Bilateral Vascular Variations at the Renal Hilum: A Case Report - Naveen Kumar; Ashwini P. Aithal; Anitha Guru; Satheesha B. Nayak (Case Reports in Vascular Medicine)
Imaging technology with its advancement in the field of urology is the boon for the patients who require minimally invasive approaches for various kidney disorders. These approaches require a precise knowledge of the normal and variant anatomy of vascular structures at the hilum of the kidney in terms of their pattern of arrangement and division. The present paper describes a bilateral anomalous arrangement of the structures at the renal hilum as well as their peculiar branching pattern which is of clinical and surgical relevance. Multiple branching of the renal vessels was observed in both kidneys due to which the hila were congested. The right renal artery immediately after its origin divided into 2 branches. The upper branch represented an aberrant artery whereas the lower branch gave 5 divisions. The left renal artery also divided into 2 branches much before the hilum as anterior and posterior divisions. The anterior branch took an arched course and gave 6 branches. The posterior branch gave 3 terminal branches before entering the renal substance. In addition to anomalous hilar structures, normal architecture of both kidneys was altered and the hilum of the left kidney was found on its anterior surface.